Wanted: perfect langga and iring a comparative content analysis - Bacalso, Danne Vie S.
This study is a content analysis of two radio programs, namely: ABS-CBN M.O.R. 101.1's Wanted: Perfect Langga and Love Radio 90.7's Iring-Iring. Their aim is to provide a venue wherein people from different walks of life can meet and interact with one another. Furthermore, this provides an analysis of how the deejay and the participants conveyed, presented and treated the topics in their conversations. Non consecutive recording of the two programs was done in order to gather the data. Recording was done from April 28, May 16, 2008. With Wanted: Perfect Langga airing from 9:00PM to 1:00AM, and Iring-Iring from 11:30AM to 1 PM; Mondays to Fridays, having ten episodes for each program. After the recording process, transcription of the data was done. It was then tabulated and the frequency of the variables and the elements were obtained. After which, the results were analyzed by looking at the elements under each variable. Analyzing the data gathered, it was found out that the two radio program's basic content were songs and plugging of their programs. However, their on-air conversations were the highlight and the main attraction of the two radio programs, which provides a venue for people from all walks of life, a chance to meet and interact on the air, some eventually face to face. This feature of the two programs involved males and females talking and sharing their experiences in life with the deejay joining in the conversations. Their plugging mainly promoted their programs and the other programs of both radio stations. However, the manner of presenting the topics in the conversations were different for each program, with Wanted: Perfect Langga using mainly whimsical and straightforward tones. While Iring-Iring also made use of both tones, but more emphasis on the use of the erotic tone. Thus, the study would recommend that further and deeper studies regarding content analysis on radio programs, regardless of format, should be done in order to measure radio's effectiveness as a communication tool. Also, this will help generate information about the sender's perspective and its effectiveness in the radio industry.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts